Analysis of the level of learning motivation among Class XI students in Physical Education learning at SMA Negeri 1 Sekincau. - Dina Amanda; Lungit Wicaksono; Riyan Jaya Sumantri; Joan Siswoyo (Jurnal Pendidikan Jasmani (JPJ), 2026)
Schools play an important role in developing students' abilities through a planned and systematic learning process. One of the subjects that has a significant contribution is Physical Education, Sports, and Health (PJOK). However, its implementation still faces various obstacles, especially related to low student learning motivation.This study aims to determine the level of learning motivation of grade XI students in participating in PJOK learning at SMA Negeri 1 Sekincau and identify the factors behind it. The type of research used is descriptive quantitative with a survey method. The study population was all grade XI students of SMA Negeri 1 Sekincau, with a sampling technique using total sampling. Data were collected through a questionnaire with a Likert scale and analyzed descriptively. The results showed that the level of student learning motivation was in the moderate category with a distribution: very high 8.20%, high 23.50%, moderate 33.33%, low 29.51%, and very low 5.46%. The main factors behind student motivation in PJOK learning are interest and perceived benefits. These findings are expected to be used as evaluation material for PJOK teachers in designing more interesting and effective learning strategies to increase students' learning motivation.